Treatment intensification with FLAG‐Ida may improve disease control in younger patients with secondary acute myeloid leukaemia: long‐term follow up of the MRC AML15 trial. (13th December 2021) - Russell, Nigel; Hills, Robert; Kjeldsen, Lars; Dennis, Mike; Burnett, Alan
Summary: Secondary acute myeloid leukaemia (AML) has a poor outcome following "3 + 7‐like" chemotherapy. While CPX‐351 has been approved for patients aged 60–75, the optimal treatment, or comparator, in younger patients is less clear. The MRC AML15 trial randomised younger patients between daunorubicin and ara‐C (DA) and DA plus etoposide (ADE) and ADE and fludarabine, cytarabine, idarubicin, and granulocyte colony‐stimulating factor (FLAG‐Ida) induction. Overall results failed to show an overall survival benefit for FLAG‐Ida despite a reduction in relapse, the outcome of patients <60 years with secondary AML compared to DA/ADE was not reported. In this group ( n  = 115) response to induction was not different [complete remission/complete remission with incomplete haematological response 81% vs. 79%), however, 5‐year overall survival and relapse free survival was superior for FLAG‐Ida [37% vs. 27%, stratified hazard ratio (HR) 0·45 (0·33–0·90) P  = 0·02 and 41% vs. 22%; stratified HR 0·54 (0·31–0·96) P  = 0·04] respectively, suggesting that younger patients with secondary AML may benefit from treatment intensification and that "3 + 7" may not be the optimal comparator in trials for this group of patients.